Hardware And Software Development Of ECG Biometric System - Chia, Pei Kiak (Universiti Sains Malaysia, 2018)
Security is a top issue in the world and nothing is completely secure. Now biometrics has been a useful security tool in recent decades because of its effectiveness in identifying and authenticating desired users versus potential intruder. ECG has been proposed as promising biometrics for human identification and authentication. The advantage of ECG biometric is highly secure, and confidential compared to fingerprint, iris, and face. However, 12 number of leads used to collect ECG signal in typical identification system is not efficient. So that, this project proposes a portable ECG detection kit that is designed by using solely by Lead 1 for ECG detection and recording. The Android application also helps to collect proper ECG signal by checking the status of subject’s ECG in this project before the subject’s ECG data is recorded. In this project, Pan-Tompkins algorithm is used as feature extraction technique of ECG fiducial points while artificial neural network is used for identification system. The performance evaluation shows that 93.65% of overall system performance and 85% of individual subject accuracy based on 10 different subject’s training data and 20 different subject’s testing. This experimental result is promising hence ECG signal is proved to be a viable modality for biometric system.